2016
DOI: 10.1007/s11832-016-0776-y
|View full text |Cite
|
Sign up to set email alerts
|

Avascular necrosis following closed reduction for treatment of developmental dysplasia of the hip: A systematic review

Abstract: BackgroundAvascular necrosis (AVN) is a significant and potentially devastating complication following the treatment of developmental dysplasia of the hip (DDH). The reported rate of AVN following closed reduction for DDH ranges from 4 to 60%, and the resultant influence on hip development remains unclear.PurposeA systematic review of the literature was undertaken to evaluate the frequency of AVN after more than 5 years of follow-up in children that underwent closed reduction at younger than 2-years of age for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 25 publications
(43 reference statements)
9
37
0
Order By: Relevance
“…Although in our study age does not play as a signi cant risk factor for AVN and re-dislocation, Similar to our results, it was also reported in previous studies [9,17,22] that age was not the risk factor of AVN after CR, while other studies gave the opposite conclusion [11,20,21]. The rate of AVN (15.4%) in this study falls into the range of the previously reported studies (10%-33%) [7] [23][24][25][26]. The most common cause of AVN is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 90%
“…Although in our study age does not play as a signi cant risk factor for AVN and re-dislocation, Similar to our results, it was also reported in previous studies [9,17,22] that age was not the risk factor of AVN after CR, while other studies gave the opposite conclusion [11,20,21]. The rate of AVN (15.4%) in this study falls into the range of the previously reported studies (10%-33%) [7] [23][24][25][26]. The most common cause of AVN is the immobilization in a position that places excessive pressure on the femoral head.…”
Section: Discussionsupporting
confidence: 90%
“…Earlier studies have reported that various possible factors related to the AVN, including the age at the onset of treatment [32] , genders [33] , the utilization of prereduction traction [34] , the severity of hip dislocation at treatment [35] , laterality (unilateral/bilateral DDH) [36] , absence of proximal femoral ossi c nucleus [37] , failed Pavlik harness treatment [38] , or adductor tenotomy [39] . However, either of these underlying factors was disputed, especially in recent evidence-based studies [40] . Whilst these variations may be a consequence of natural variation due to the relatively small case numbers, different cases selection or the diversities in therapeutic regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of AVN varies widely (0 ~ 92.4%), mainly due to the lack of uni ed diagnostic criteria and some different understandings. Bradley et al [24] conducted a retrospective study on AVN incidence after CR, and it was 10% among 441 DDH children (538 hips) on an average follow-up time of 7.6 years.…”
Section: Discussionmentioning
confidence: 99%